Raised blood pressure in Italy: results of the CUORE Project-health examination survey 2018-2019. (30th September 2020) - Donfrancesco, C; Di Lonardo, A; Minutoli, D; Lo Noce, C; Buttari, B; Profumo, E; Bellisario, P; Giampaoli, S; Galletti, F; Palmieri, L
Abstract: Background: The WHO Global Action Plan for the Prevention of Non-Communicable Disease (WHO-NCD) recommends a 25% relative reduction in the prevalence of raised blood pressure (RBP) by 2025. Prevalence of RBP and mean blood pressure in the Italian general adult population measured in the 2018 CUORE Project-Health Examination Survey are presented to investigate if Italy can reach this target. Methods: Within the health examination survey conducted in 2018-2019, representative random samples of resident population, aged 35-74 years, stratified by age and sex (822 men and 869 women) were examined in 8 Italian Regions from the Northern, Central and Southern Italy. Blood pressure was measured by automated oscillometric device using standardized procedures and methods; mean level of two measurements are here considered. RBP is defined as systolic and/or diastolic blood pressure equal or greater than 140/90 mmHg or being under specific drug treatment. The survey is funded by the Italian Ministry of Health-CCM. Results: Preliminary analysis shows that prevalence of RBP is 43% (95% C.I. 40-47) in men and 32% (29-36) in women. Prevalence of persons with raised blood pressure and not receiving pharmacological treatment is 19% (15-22) in men and 9% (5-12) in women. In men and women prevalence of raised blood pressure is significantly higher in the Southern Regions. Mean value of systolic blood pressure is 131 mmHg (130-132) in men and 122 mmHg (121-123) in women. Mean value of diastolic blood pressure is 77 mmHg (76-78) in men and 73 mmHg (72-74) in women. Conclusions: Preliminary data underline that RBP is commonly observed in the Italian adult population. However, in comparison to data measured within the CUORE Project 10 years earlier, prevalence of RBP and mean blood pressure are declining, facilitating the meeting of WHO-NCDs target. Key messages: Raised blood pressure is commonly observed in the Italian general adult population. If confirmed, in the last ten years prevalence of raised blood pressure and mean blood pressure are declining in the Italian general adult population.